Fashioning intellectual property : exhibition, advertising and the press 1789-1918 - Richardson, Megan; Thomas, Julian, 1963- (Cambridge : Cambridge University Press, 2012)
'Vigorous public debate about intellectual property has a long history. In this assessment of the shifting relationships between the law and the economic, social and cultural sources of creativity and innovation during the long-nineteenth century, Megan Richardson and Julian Thomas examine the'fashioning' of the law by focusing on emblematic cases, key legislative changes and broader debates. Along the way, the authors highlight how, in'the age of journalism', the press shaped, and was shaped by, the idea of intellectual property as a protective crucible for improvements in knowledge and progress in the arts and sciences. The engagement in our own time between intellectual property and the creative industries remains volatile and unsettled. As the authors conclude, the fresh opportunities for artistic diversity, expression and communication offered by new media could see the place of intellectual property in the scheme of law being reinvented once again'--
Part I. The Journalism Age -- Grub Street biographers -- Author-journalists -- Agitators and dissenters -- End of the property right -- Part II. The Exhibition Effect -- Patent inadequacies -- Exhibition fever -- Lessons and compromises -- Rise of advertising -- Part III. The Author-Brand Continuum -- Rethinking'romantic' authorship -- The artist in an age of mechanical reproduction -- From fashion to brand -- Closing the categories.
Includes bibliographical references (p. 166-185) and index.
Keywords: Copyright -- Great Britain -- History -- 19th century